Ação do fungo entomopatogênico Aschersonia aleyrodis e de derivados de nim no manejo de Aleurocanthus Woglumi ASHBY (hemiptera: aleyrodidae) em citros - Lemos, Kleydejany Lima de (2008)
The citrus blackfly, Aleurocanthus woglumi, is a threat to the citricultures of all the country for if treating to a quarantine plague A2 and, in function of the impacts that the adopted measures of control can cause on natural ecosystems. The objectives of this work had been to evaluate the action of fungus entomopatogênico Aschersonia aleyrodis and of aquous extracts of leves and seeds of nim Azadirachta it indicates A. Juss on the black fly. Leves of Citrus latifolia, proceeding from an orchard located in the municipality of São José de Ribamar - MA, contend nymphs of the blackfly had been immersed for a period of 5 seconds in different concentrations of fungi A. aleyrodis (1 x 105 , 1 x 106 , 1 x 107 x and 1 x 108 x conídios/mL) and in different concentrations of the aquous extract of leves and seeds of nim (1,0; 2,5; 5,0; e 10.0%). After the immersion, the leves had been placed in conditioned plates of Petri and in climatized chamber (26 ± 1º C, 80 ± 5 UR and fotofase of 12 hours). The evaluations had been carried through to the 3, 6 and 9 days after the immersion, counting themselves the number of insects livings creature. Mortality was corrected by the formula of Abbott (1925) and the data analyzed for the not-parametric test of Nemenyi 5% of probability. As much entomopathogenic fungi, A. aleyrodis, as aquous extracts leaf and seeds of nim if had shown efficient in the control of the blackfly, causing 100% of mortality in the concentrations highest, 1 X 107 x and 1 X 108 conídios/mL of the A. aleyrodis and 5,0 and 10.0% of the aquous extracts leaf and seeds of nim , constituting an excellent alternative in the control of this plague, a time that the indiscriminate use of chemical insecticides provokes contaminations in the environment.